Stability and change in relationships - Vangelisti, Anita L.; Reis, Harry T.; Fitzpatrick, Mary Anne, 1949- (Advances in personal relationships (Cambridge, England), 2002)
"Understanding interpersonal relationships requires understanding actors, behaviors, and contexts. This volume presents cutting-edge research from a variety of disciplines that examines personal relationships on all three levels. The first section focuses on the factors that influence individuals to enter, maintain, and dissolve relationships. The second section emphasizes ongoing processes that characterize relationships and focuses on issues such as arguing and sacrificing. The third and final section demonstrates that the processes of stability and change are embedded in social, cultural, and historical contexts. Chapters address cultural universals as well as cross-cultural differences in relationship behaviors and outcomes. The emergence of new relational forms, such as the interaction between people and computers, is also explored. Stability and Change in Relationships will be of interest to individuals in a broad range of fields including psychology, sociology, communication, gerontology, and counseling."--Publisher's description